Comparative Analysis of Microfinance Policy Frameworks and Legislation of Selected Countries - Brown, Matthew; Jacobs, Ruth (International Finance Corporation, Washington, D.C., 2017)
This comparative study seeks to contribute to the ongoing dialogue and development of policy frameworks specifically in Azerbaijan and Central Asia. Given the IFC’s current transformation work in this area, the countries that have been included in this study are Azerbaijan, Kazakhstan, Kyrgyzstan, Mongolia, and Tajikistan. To incorporate the experience of countries outside this region, the study includes Bolivia, Bosnia and Herzegovina (BiH), and Morocco. All of these countries have a legal system and policy framework that incorporates microfinance. In most cases, these countries have adopted specialized legislation that creates a new legal window for MFIs that is distinct from existing and traditional types of financial institutions. Despite these similarities there are some notable differences among the policy frameworks that are explored in the sections that follow. This study is divided into four sections with three annexes. The first section explores microfinance in Azerbaijan and the Central Asian contexts. The second section analyzes and compares the structure and nature of the various policy frameworks and approaches to regulation and supervision. The third section compares permitted activities and restrictions among the different institutional types. The fourth section looks at ownership requirements and issues related to MFI transformation. Macroeconomic and microfinance specific data for each of the countries has been compiled in tables in annex one. Annex two contains legislative profiles of each of the countries organized under various categories. Annex three lists the primary legislation for microfinance for each of the countries. Finally, the body of work reviewed in preparation of this study is noted in the section entitled resource materials.